Detecting Biological Motion for Human–Robot Interaction: A Link between Perception and Action - Vignolo, Alessia; Noceti, Nicoletta; Rea, Francesco; Sciutti, Alessandra; Odone, Francesca; Sandini, Giulio (Frontiers in Robotics and AI, 2017)
One of the fundamental skill supporting safe and comfortable interaction between humans is their capability to understand intuitively each other's actions and intentions. At the basis of this ability is a special-purpose visual processing that human brain has developed to comprehend human motion. Among the first "building blocks" enabling the bootstrapping of such visual processing is the ability to detect movements performed by biological agents in the scene, a skill mastered by human babies in the first days of their life. In this paper we present a computational model based on the assumption that such visual ability must be based on local low-level visual motion features which are independent of shape, such as the configuration of the body, and perspective. Moreover, we implement it on the humanoid robot iCub, embedding it into a software architecture that leverages the regularities of biological motion also to control robot attention and oculo-motor behaviors. In essence, we put forth a model in which the regularities of biological motion link perception and action enabling a robotic agent to follow a human-inspired sensory-motor behavior. We posit that this choice facilitates mutual understanding and goal prediction during collaboration, increasing the pleasantness and safety of the interaction.